Cyclic response of CLT Post-Tensioned Walls: Experimental and numerical investigation. (15th November 2021) - Pozza, Luca; Benedetti, Luca; Tomei, Valentina; Ferracuti, Barbara; Zucconi, Maria; Mazzotti, Claudio
Highlights: Advanced low damage post-tensioned CLT system is presented employing innovative dampers. Results of Full-scale cyclic tests on post-tensioned CLT wall systems are provided. Single and double wall configurations were tested. Different dampers' pattern and different post-tensioning levels were considered. A predictive non-linear numerical model for post-tensioned CLT systems is proposed and validated. Abstract: This paper presents the main outcomes of full-scale cyclic tests on CLT post-tensioned walls. Investigated systems were constituted by rocking dissipative timber walls, whose main features were the re-centering of walls, low damage in case of seismic actions, additional hysteretic dissipation, and easy replacement of dampers. Referring to previous experimental campaign on LVL and CLT structures available in literature, the proposed post-tensioned CLT wall system was conceived employing an innovative and replaceable damping system and realizing all the technological details in order to minimize local and global damages due to horizontal cyclic loading. Two kinds of post-tensioned systems were tested: single wall and double walls with different set-up configurations and patterns of the dampers. Specifically, two different levels of initial post-tensioning force were applied and different patterns of damper system were experimentally investigated in order to define the energy dissipation contribution provided by the individual damper types installed. These different configurations were investigated by using the same CLT wall system which, despite having been subjected to repeated cyclic tests, showed limited residual damage and therefore fulfilled the low-damage requirement. In order to properly design the experimental set-up, an advanced Finite Element nonlinear numerical model was developed in the OpenSEES framework and then calibrated on the local response of the individual components of the system. Model calibration is presented and the comparison with the experimental results is critically discussed both in terms of local and global response of the PT-wall systems. The proposed model well captured the hysteretic behaviour of the wall system highlighting the reliability of the modelling strategy.